Commercialization of agricultural research and biotechnology stakeholder consultation workshops: Final report - Ahmed, Akhter; Bakhtiar, M. Mehrab; Ghostlaw, Julie; Parvin, Aklima; Khan, A. S. M. Mahbubur Rahman; Sultana, Nasreen; Siddique, Rezaul Karim; Kundu, Subrata Kumar (International Food Policy Research Institute, 2021)
From December 6-10, 2020, USAID organized and IFPRI facilitated five virtual stakeholder consultation workshops on agricultural research and biotechnology, bringing together relevant stakeholders involved in crop and non-crop agriculture from Barishal, Cox’s Bazar, Dhaka, Jashore, and Khulna districts in southern Bangladesh. This format aimed to capture the views and perceptions of a range of relevant actors on the status, opportunities and challenges, and recommendations for improving agricultural research and biotechnology. This report presents the subjective views of participants who are affected by and have a stake in these discussions, from value chain actors who have had challenges cultivating certain varieties and raising certain breeds due to climate-related challenges to researchers who are developing new varieties and breeds accounting for these ground-level challenges. Although the authors have substantiated parts of this report with primary and secondary data sources, the major thrust of this report is to communicate perspectives as they were framed during the workshops. Although stakeholder responses reflect varying knowledge levels of biotechnology among participants, some of which may be convoluted or inaccurate, this report preserves the diversity of stakeholder input as an honest reflection of the opinions received.